An assessment of amount, distribution and use of urban green spaces in small towns of the Eastern Cape - Radebe, Denis Siphosihle (Rhodes University, Faculty of Science, Department of Environmental Science, 2019)
Most regions of the developing world are experiencing large-scale urbanisation, with urban population growth outstripping rural growth. This is most marked in small and medium-sized towns as opposed to megacities. Urbanisation is associated with numerous changes in social, economic and ecological states and dynamics. A key one, of interest in this study, is the sustainability and liveability of the growing towns and cities. The retention, provision and maintenance of multifunctional urban green infrastructure are a core strategy in this regard. This study therefore sought to assess the amount, distribution and use of urban green spaces within South Africa using small towns of the Eastern Cape. The primary research included sixteen aerial images of which eight were historical aerial photographs and another eight were the latest aerial images of the selected study towns. Historical and latest aerial images were digitised to classify the types and calculate the amount of urban green space. GIS mapping, interviews and focus group discussions were conducted with urban residents to understand how these green spaces are used. The analytical tools in this study derived from social science included household surveys of 180 randomly selected respondents in small towns. Fifteen types of green spaces were identified in the sample towns. The study further revealed that green spaces are not distributed equally in different suburbs of small towns, generally being less green spaces, especially formal parks and recreation areas, in poorer areas. The results indicated a decline of green spaces with urbanisation, and most marked in fast growing towns. The results suggested that urban residents frequently visited urban green spaces, with most respondents favouring the use of green spaces for social and cultural benefits. How use of different spaces was strongly gender related, with males favouring less developed green space types (such as commonages and woodlands) and females for formal areas such domestic and institutional gardens and churchyards. Respondents also identified various challenges associated with using and accessing urban green spaces, with pollution, crime and lack of maintenance in particular. The study shows the importance of GIS as a mapping tool that can be used to provide information for ecological planning in rapidly changing urban environment. The research process generated several lessons that need to be taken into consideration when designing urban landscapes, most importantly relating to the diversity, quantity, quality and maintenance of urban green spaces.
Keywords: Urban ecology (Sociology) -- South Africa -- Eastern Cape; Small cities -- South Africa -- Eastern Cape; City planning -- South Africa -- Eastern Cape; Recreation areas -- South Africa -- Eastern Cape; Open spaces -- South Africa -- Eastern Cape